Analisis Struktur Modal Pada Perusahaan Asuransi Yang Terdaftar Di Bursa Efek Indonesia Periode 2019-2022 - Mursita Ismayanti; Eko Triyanto (CV. ALIM'SPUBLISHING, 2024)
Knowing the results of tests on the influence of profitability, business risk, sales growth and company size on the capital structure of insurance companies listed on Indonesia Stock Exchange is the aim of this research. The theory used is pecking order theory. Purposive sampling is the chosen sampling method. There are 18 insurance companies as sample companies registered on the Indonesian Stock Exchange and this has been processed for 4 years, resulting in 72 observations. The type of data used is secondary data in the form of financial reports of insurance companies that are registered on the Indonesia Stock Exchange for the 2019-2020 period. The analytical method used is multiple linear testing using the SPSS version 27 application. After testing and analyzing the data, the results show when partially profitability has a negative influence on capital structure. Partially, business risk, sales growth and company size have no influence on capital structure.